Experimental Analysis of Srtm Model by Image Processing and Geostatistical Methods - V. Kuzyakina, M.; A. Gura, D.; A. Mishchenko, Yu.; A. Gordienko, D. (International Journal of Engineering and Technology, 2018)
This article compares the image processing and geostatistical methods of GIS. They proposed the application of these methods to restore the quality of the well-known digital elevation model SRTM degraded sections using the example of the Krasnodar Territory. The conclusions are drawn also about the quality of modeling for test sites with different types of relief â€“ flat, hilly and mountain. The best results were achieved for the method of bicubic interpolation.Â